ANALISIS PENGARUH FOCUS FILM DISTANCE PADA PESAWAT RONTGEN GENERAL PURPOSE - Setia Gunawan Mendropa; Samser Nababan (JURNAL MUTIARA ELEKTROMEDIK, 2018)
Analysis of the influence of Distance film focus (FFD) on general purpose X-ray on variations of 80 cm, 100 cm and 120 cm FFD using Allignment Beam with a height of 15 cm and collimator test tool as the object of research at the Radiology Installation of Amanda Brastagi General Hospital. The aim is to determine and analyze the accuracy of the center point of the X-ray beam and the density of radiographic films. To diagnose, X-ray diagnostics of this unit must be precise and accurate in determining the location or place of interference in the human body. So we need to test the accuracy of the center point of the X-ray beam, so that the output of the X-ray beam from X-ray tube to the patient is still in parallel and there is no shift in angle or distance on the X-ray tube.After research and analysis, angular deviations are produced which are still within the predetermined tolerance limit of 3my.